Depreciation in Local Government - Still the Problems Continue - Pilcher, Robyn (Routledge, 2018)
At least as far back as the 16th century, depreciation has been the subject of many debates within organisations, academia and the professional world. In 1912, Leake (cited in Brief 1967, p. 27) stated that 'because it closely concerns Profit and Loss, the subject of Depreciation and Wasting Assets is of universal importance ...'. In 2002, the then Australian Capital Territory (ACT) Deputy Chief Minister and Treasurer, Ted Quinlan (cited by Awty 2002, p. 40), asked: 'Is depreciation appropriate on all public assets or does it distort the true bottom line of the public sector ..?' In 2013, an asset manager from a NSW city council said 'I think the discussion [about depreciation] is worthwhile and an "old chestnut" that keeps rearing its ugly head …' (Accounting and Engineering (XAE) Public Forum, July 2013).2 Here are three people, 90 years apart, saying virtually the same thing confirming my belief that the depreciation discussion is, as Sterling (1975, p. 28) so succinctly said, a case of 'recycled ideas without resolving issues' observation. It appears that little, if anything, has changed when one considers the problems experienced world-wide concerning valuation, depreciation and maintenance of infrastructure assets (Barnes & Lord 2017; Marsh & Fischer 2013; Pryor 2013). This chapter details asset management and depreciation concerns as applied to transport infrastructure (concentrating on roads) in local government authorities (LGAs) in Australia and New Zealand (NZ). Some of the current and future issues include those raised in a discussion forum over a period of five years. These highlighted different aspects associated with asset management and depreciation that can be seen to still be causing many a headache for engineers and accountants alike. There are three aims for this particular chapter. The first outcome will be to bring to the attention of academics, once again, the problems associated with asset management and depreciation by examining the past, the present and the future. The second goal is to raise the various issues still in need of research and the final aim is to raise yet another question—can a 'recycled idea' like depreciation ever be resolved? This chapter is only the tip of the iceberg when it comes to the amount of research still to be undertaken.